1997
DOI: 10.1161/01.res.80.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Angiotensin-Converting Enzyme Expression and Activity by Shear Stress

Abstract: Shear stress caused by the frictional forces of a fluid moving over a cell monolayer is an important regulator of gene expression. In this study, we investigated the effect of shear stress on angiotensin-converting enzyme (ACE) expression and promoter activity in vitro and on local vascular ACE activity in vivo. ACE activity measured in bovine pulmonary artery endothelial (BPAE) cells was reduced by 49.5% after exposure to a shear stress of 20 dyne/cm2 for 18 hours. Short-term shearing (2 hours) elevated ACE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 28 publications
3
72
1
2
Order By: Relevance
“…Human LDL (Intracel, Frederick, MD) was diluted to a 0.1 mg/ml concentration in DMEM. A 5-ml volume of DMEM/LDL was exposed to 18 dyne/cm 2 shear stress for 1 h by using a cone-plate viscometer provided by Andrew Greene (Medical College of Wisconsin), as described (16). A static, control solution of LDL was incubated in an identical setup without rotation of the cone.…”
Section: Methodsmentioning
confidence: 99%
“…Human LDL (Intracel, Frederick, MD) was diluted to a 0.1 mg/ml concentration in DMEM. A 5-ml volume of DMEM/LDL was exposed to 18 dyne/cm 2 shear stress for 1 h by using a cone-plate viscometer provided by Andrew Greene (Medical College of Wisconsin), as described (16). A static, control solution of LDL was incubated in an identical setup without rotation of the cone.…”
Section: Methodsmentioning
confidence: 99%
“…A confluent monolayer of BAEC grown in a 100-mm dish was exposed to nonpulsatile, laminar shear stress in a shear medium (phenol red-free DMEM containing 0.5% FBS and 25 mM HEPES, pH 7.4) by rotating a Teflon cone (0.5°cone angle) as we described previously (21,43). Cells were exposed to an arterial level of shear stress (15 dyn/cm 2 ) (3,21).…”
Section: Methodsmentioning
confidence: 99%
“…The lentiviral induction is shown to result in an increase of LKLF protein that was correctly targeted to the endothelial nucleus (Figure 7, A and B) and is similar to the LKLF increase and nuclear localization that is observed under prolonged shear stress ( Figure 7, C and D). Seven days after transduction of HUVECs with the mock or LKLF lentivirus, real-time RT-PCR was used to study the expression of the following known shear-regulated genes: endothelin-1, 12 adrenomedullin, 14 ACE, 13 and eNOS. 11 The results reveal consistent transcriptional regulation of these genes by prolonged expression of LKLF in the Figure 6.…”
Section: Lklf Regulates Transcription Of Genes Involved In Vascular Tmentioning
confidence: 99%
“…10,11 Well-known examples are the shear-repressed endothelin, 12 angiotensin-converting enzyme (ACE), 13 and adrenomedullin, 14 and the shear-induced endothelial nitric oxide synthase (eNOS). 11 It was recently demonstrated that LKLF potently induces functional eNOS expression by directly binding its promoter.…”
mentioning
confidence: 99%